Mid Term Appraisal of Ninth Five Year Plan (1997-2002) Government of Gujarat - Planning Commission (Planning Commission, 1997)
Two third of population in Gujarat is engaged in Agriculture and earn livelihood directly from the occupation Besides, the Occupation provides indirect employment to large portion of population in agro-base secondary and tertiary occupations. Thus prosperity and well being of people in Gujarat are closely linked with the agriculture. Hence the planning for Successful and rapid development of agriculture ha got direct implication of the well being of the population of the State. The pace of its development should be rapid enough so as its implication on the well being of the people nay not be marked by the rate of growth of population.
Government of Gujarat
Government of Gujarat
Keywords: Agricultural Research Education; Community Development Panchayats; Sardar Sarovar (Narmada) Project; Village Cottage and Rural Industries; Geology & Mining; World Bank Aided Project; Gujarat State Roads Development Corporation; Environment Pollution; Food And Drugs; Decentralized District Planning; Information And Broadcasting; Mid-Day Neal Scheme